2017
DOI: 10.3892/or.2017.5413
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol enhances the radiosensitivity of nasopharyngeal carcinoma cells by downregulating E2F1

Abstract: Identification of safe, effective radiosensitizing agents is urgently needed to improve the outcome of radiotherapy in nasopharyngeal cancer (NPC). In this study, we assessed the ability of the polyphenol resveratrol to act as a radiosensitizer in vitro and in vivo. CNE-1 cells were treated with 50 µM resveratrol for 24 h, then irradiated. E2F transcription factor 1 (E2F1) was stably knocked down and overexpressed using lentiviruses. A xenograft model of NPC was established in nude mice using CNE-1 cells. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
3
19
0
1
Order By: Relevance
“…When combined with radiation therapy, resveratrol has been shown to augment the anti-cancer effects of radiation in both in vitro and in vivo studies [320][321][322][323][324], as reviewed in [250]. For instance, resveratrol has proven in the past to offer radiosensitizing effects in nasopharyngeal cancer cells via inhibition of E2F transcription factor, colony-forming activities, and the induction of G 1 phase cell cycle arrest [325]. Apigenin has been shown to enhance the apoptotic effects of radiation in SQ-5 human lung carcinoma cells by increasing the protein expression of WAF1/p21 while decreasing protein levels of Bcl-2 [326].…”
Section: Radiosensitizing Effects Of Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…When combined with radiation therapy, resveratrol has been shown to augment the anti-cancer effects of radiation in both in vitro and in vivo studies [320][321][322][323][324], as reviewed in [250]. For instance, resveratrol has proven in the past to offer radiosensitizing effects in nasopharyngeal cancer cells via inhibition of E2F transcription factor, colony-forming activities, and the induction of G 1 phase cell cycle arrest [325]. Apigenin has been shown to enhance the apoptotic effects of radiation in SQ-5 human lung carcinoma cells by increasing the protein expression of WAF1/p21 while decreasing protein levels of Bcl-2 [326].…”
Section: Radiosensitizing Effects Of Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…Resveratrol exerts anticancer effects through mediating the function of molecular targets associated with cell proliferation, cell cycle and apoptosis [ 7 ]. Recently, research has revealed the potent anti-proliferative and pro-apoptotic effects of resveratrol in NPC [ 8 ]. However, the molecular mechanism involved in the effects of resveratrol in NPC is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…18 Aberrant E2F1 upregulation, which is associated with malignant processes and poor prognosis, is frequently observed in many kinds of human cancers. [19][20][21][22] Moreover, E2F1 is also associated with radiosensitivity 23 and chemosensitivity 24,25 in cancer cells. While some findings showing that E2F1 is involved in cell senescence and apoptosis may suggest its dual role in tumor formation, 26 several events accelerating the development of cancer may neutralize the tumor-suppressive functions of E2F1.…”
mentioning
confidence: 99%